Persistent Lymphopenia as a Predictor of in-Hospitality in Septic Patients at Dr. Sardjito Hospital - Juvita Kurniawan (Acta Interna The Journal of Internal Medicine, 2020)
Background: Sepsis, a life-threatening organ dysfunction caused by deregulation of body response to an infection with a high mortality rate. Pro-inflammatory cytokines are related to early mortality related sepsis, and immune dysfunction and suppression characterized by lymphocyte loss are related to late mortality. Persistent lymphopenia is a good biomarker for immunosuppression and predicts mortality in sepsis patients. Lymphocyte counts are easily measured and cheaper than other inflammation marker for sepsis.Aims: The objective of this study was to determine whether persistent lymphopenia has a predictive value for mortality in septic patients at Dr. Sardjito General Hospital.Methods: This study was a retrospective cohort study, sepsis and lymphogenic patients admitted to Internal Medicine ward between January 1, 2016 and December 31, 2017. Lymphocytes were count at day 1 and 4 following the diagnosis of sepsis. Persistent lymphopenia was defined as an absolute lymphocyte count of 1.62x10/μL or less on day 4. The primary outcome was mortality at the end of hospitalization.Results: 126 adult patients, 101 with persistent lymphopenia, 25 non-persistent lymphopenia, 47 patients died (37.3%). Patients with persistent lymphopenia significantly at risk of death (P=0.003, OR 5.66, 95% CI 1.59-20.13) than non-persistent lymphopenia. Logistic regression was used to account for potential confounding factors, persistent lymphopenia (p = 0.003, OR 8.01, 95% CI 2.04-31.45) and skin and soft tissue infection (p= 0.017, OR 2.94, 95% CI 1.21-7.14) were significantly associated with mortality in sepsis patients at Dr. Sardjito General Hospital.Conclusion: Persistent lymphopenia predicts mortality in adult patients with sepsis at Dr. Sardjito GeneralHospital.